2004
DOI: 10.1007/s11104-005-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of thicket to savanna reduces soil quality in the Eastern Cape, South Africa

Abstract: Xeric succulent thicket in the Eastern Cape, South Africa has been used for farming goats since the early 1900s. This habitat is characterised by a dense cover of the succulent bush Portulacaria afra and by a warm, semi-arid climate with evenly distributed annual rainfall of 250-400 mm. Heavy browsing by goats results in the loss of P. afra and transforms the thicket to an open savanna dominated by annual grasses. Eight fence-line comparisons between thicket and savanna were used to investigate differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 37 publications
(31 reference statements)
1
59
0
1
Order By: Relevance
“…Figure 4 shows, nevertheless, that poorly permeable soils can also support minimal species richness. Although it is tempting to think that such soils may have been overgrazed, which can result in reduced plant cover and species richness as well as infiltrability (Mills and Fey 2004b), at least some of these soils may simply have a high pH or low nitrogen content which, as Fig. 4 shows, ensures low species richness in this dataset.…”
Section: Plant Covermentioning
confidence: 98%
“…Figure 4 shows, nevertheless, that poorly permeable soils can also support minimal species richness. Although it is tempting to think that such soils may have been overgrazed, which can result in reduced plant cover and species richness as well as infiltrability (Mills and Fey 2004b), at least some of these soils may simply have a high pH or low nitrogen content which, as Fig. 4 shows, ensures low species richness in this dataset.…”
Section: Plant Covermentioning
confidence: 98%
“…A study conducted in the sub-tropical humid grasslands in South Africa indicated that the decline in grass (vegetative) cover from 100% to 0%-5% reduced the SOC pool by 1.25 kg/m 2 and the soil organic N (SON) pool by 0.074 kg/m 2 [20], There were also attendant declines in the C:N ratio and proportion of SOC and SON in the silt + clay fraction with the decline in aerial grass cover which negatively affected ecosystem functions of the acidic sandy loam soils. Similarly, transformation of a thicket vegetation to an open savanna (dominated by grasses) due to intensive grazing decreased soil quality in the Eastern Cape region of South Africa [21]. Indeed, savanna soils have lower SOC concentration and a greater tendency to crust than thicket soils because of the decreased quantity and stability of structural aggregates.…”
Section: Soil Organic Carbon and Its Impact On Soil Qualitymentioning
confidence: 99%
“…The amount of rainfall not intercepted by vegetation (i.e. 'throughfall'), largely determines the amount of surface runoff (Mills and Fey, 2004). Most studies mentioned only throughfall, but 'interceptional loss' (i.e.…”
Section: And Listed Inmentioning
confidence: 99%
“…LeMaitre et al, 1999;van Luijk et al, 2013). For instance, plant communities in semi-arid scrublands take up water more efficiently than plants in sub-humid ecosystems(Le Maitre et al, 1999;Mills and Fey, 2004). Lower vegetation cover in…”
mentioning
confidence: 99%